Insights about sustainable biodiesel production from microalgae biomass: A review - Rahul S, Michael; MA, Sundaramahalingam; CS, Shivamthi; R, Shyam Kumar; P, Varalakshmi; S, Karthikumar; J, Kanimozhi; R, Vinoth Kumar; S, Sabarathinam; I, Ganesh Moorthy; A, Pugazhendhi (International journal of energy research, 2021)
Summary Production of biodiesel from microalgae can be categorized as a symbiotic engineering solution focusing on energy and environmental problems. This review presents a collection of recent methods adopted for the production of biodiesel from microalgae. Microalgae are tiny cell factories which yield a large quantity of biomass by employing different methods of cultivation and using different types of harvesting techniques. Different strategies like nutrient starvation and micronutrient supplementation for hyper lipid accumulation to produce biodiesel for competing with the high market demand for fossil fuel are discussed. The use of different cultivation techniques for increasing the algal biomass in the recent scenario is focused. Also, improvement in the design strategies of bioreactors like the open pond, photobioreactors, and hybrid systems is included in the review. Further, diverse technologies for lipid improvement, including manipulating the bioprocess parameters and genetic engineering, are addressed. Also, microalgae for biorefinery approaches solve pollution problems, and its biomass can be used for biodiesel production which is elaborated in detail. The possibility of production of biodiesel from microalgae at a larger scale by overcoming the main bottlenecks in different steps of algal growth like high biomass cultivation, investment factor, and implementation of biorefinery approaches to address the current energy demand is also proposed.